No-wait two-machine permutation flow shop scheduling problem with learning effect, common due date and controllable job processing times. Issue 6 (19th March 2018) - Gao, Fu; Liu, Mengqi; Wang, Jian-Jun; Lu, Yuan-Yuan
Abstract: We consider a two-machine no-wait permutation flow shop common due date assignment scheduling problem where the processing time of a job is given as a function of its position in the sequence and its amount of resource allocated to this job. The common due date (CON) assignment method means that all the jobs are given a common due date. We need to make a decision on the common due date, resource allocation and the sequence of jobs to minimise total earliness, tardiness, common due date cost and total resource cost. We show that the problem remains polynomially solvable under the proposed model.